1996
DOI: 10.2118/96-06-03
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Modelling Of Wellbore Backflow

Abstract: Production from reservoirs with large permeability contrasts or reservoirs consisting of several non-communicating layers can result in significant crossflow between the layers through multilayer wells. This entails the backflow of reservoir fluids from the wellbore to the reservoir. Standard line source/sink methods for handling wells in reservoir simulators are unable to cope with backflow because the wellbore is assumed to have the same saturations as the reservoir. To simulate backflow accurately, the well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Leary, Peter et al [7] introduced the prospect of rock flow stimulation in the basement of enhanced geothermal system (EGS) by using wellbore temperature data, and the effective modeling of wellbore backflow was introduced by Sharma et al [8]. e related research on oil well pump simulation has been reported in literature, such as the simulation study of a double acting reciprocating oil well pump based on AMESim carried out by Wuhan Second Ship Design and Research Institute [9], and Northeast Petroleum University [10] has carried out numerical simulation calculation on the clearance flow and valve clearance flow model of oil well pump based on CFD technology, and the calculation results are visualized. e digital twin system of centrifugal pump disclosed by Siemens AG [11] of the United States patent right is established.…”
Section: Prefacementioning
confidence: 99%
“…Leary, Peter et al [7] introduced the prospect of rock flow stimulation in the basement of enhanced geothermal system (EGS) by using wellbore temperature data, and the effective modeling of wellbore backflow was introduced by Sharma et al [8]. e related research on oil well pump simulation has been reported in literature, such as the simulation study of a double acting reciprocating oil well pump based on AMESim carried out by Wuhan Second Ship Design and Research Institute [9], and Northeast Petroleum University [10] has carried out numerical simulation calculation on the clearance flow and valve clearance flow model of oil well pump based on CFD technology, and the calculation results are visualized. e digital twin system of centrifugal pump disclosed by Siemens AG [11] of the United States patent right is established.…”
Section: Prefacementioning
confidence: 99%
“…유체를 생산중이거나 폐쇄(shut-in)상태 에 있는 유정에서는 각 층간의 추가적인 압력차이를 분 석함으로써 시추정 층간유동을 감지할 수 있다 (Petricola and Watfa, 1993;Pederson et al, 1998;Zhu et al, 2002;Sommerauer and Zerbst, 2006). 이산 시추정 모델 (discretized wellbore model)은 시추정 층간유동을 모사 하기에 적합한 것으로 알려져 있다 (Sharma et al, 1996). 두 개의 층으로 이루어진 다층 저류층에서 수직정을 통해 하나의 층만 천공 하였을 경우, 해당 층에서만 유체 의 생산이 이루어진다.…”
Section: Figunclassified